2021
DOI: 10.12928/eltej.v4i1.3702
|View full text |Cite
|
Sign up to set email alerts
|

The suitability of foreign language teaching in childhood according to the CLIL approach: the foreign language teachers' attitudes

Abstract: This paper presents the results of a research into the foreign teachers' attitudes towards the first foreign language (FL 1) teaching according to the CLIL approach. The first foreign language teachers (FL 1 teachers) should have carried out their FL 1 lessons using the CLIL approach. The results of the twelve interviews: teachers agree upon the importance of the education process of teachers-to-be, for any teacher working at an early level should have completed a BA in class teaching and should have acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Various studies investigating CLIL practices in different educational settings revealed that during implementation, teachers experience a variety of challenges. Some of the problems identified in the studies conducted in the European context include insufficient teacher training programs and institutional support for professional growth (Banegas, 2012;Denman, Tanner & de Graaff, 2013); low language proficiency levels of students that lead to comprehension problems and unsatisfactory development of students' productive skills (Pladevall-Ballester, 2015); teachers' inadequate expertise in non-linguistic subject-areas (Smajla, 2021); classroom management issues experienced during instruction; the amount of time required for lesson planning and class preparation (Pladevall-Ballester, 2015); and insufficient teaching materials (Roiha, 2014). In a recent cross-cultural study, exploring the perceptions of managers and teachers about CLIL in Spain, Italy, and Turkey, Korbek (2019) found that support for teacher training, material design and use, and collaboration among teachers within their full schedule are the challenges prevalent in all three contexts.…”
Section: Ict Use In Clil Classroomsmentioning
confidence: 99%
“…Various studies investigating CLIL practices in different educational settings revealed that during implementation, teachers experience a variety of challenges. Some of the problems identified in the studies conducted in the European context include insufficient teacher training programs and institutional support for professional growth (Banegas, 2012;Denman, Tanner & de Graaff, 2013); low language proficiency levels of students that lead to comprehension problems and unsatisfactory development of students' productive skills (Pladevall-Ballester, 2015); teachers' inadequate expertise in non-linguistic subject-areas (Smajla, 2021); classroom management issues experienced during instruction; the amount of time required for lesson planning and class preparation (Pladevall-Ballester, 2015); and insufficient teaching materials (Roiha, 2014). In a recent cross-cultural study, exploring the perceptions of managers and teachers about CLIL in Spain, Italy, and Turkey, Korbek (2019) found that support for teacher training, material design and use, and collaboration among teachers within their full schedule are the challenges prevalent in all three contexts.…”
Section: Ict Use In Clil Classroomsmentioning
confidence: 99%